Impact of Environmental Regulations on Sustainable Livestock Farming Practices in Pakistan - Aziz, Wasim (American Journal of Livestock Policy, 2024)
Purpose: The aim of the study was to assess the impact of environmental regulations on sustainable livestock farming practices in Pakistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that in developed economies, stringent regulations have prompted farms to adopt advanced technologies and management practices. These include precision feeding systems, methane capture technologies, and improved waste management techniques to minimize environmental impact. Compliance with regulations often necessitates substantial investments in infrastructure and operational adjustments, driving farms towards more efficient resource utilization and reduced emissions. Consequently, sustainable practices like rotational grazing, organic feed alternatives, and biodiversity conservation have gained prominence, aligning with regulatory goals of reducing greenhouse gas emissions and preserving natural habitats. Conversely, in developing economies, where regulatory frameworks may be less robust or unevenly enforced, the impact varies. Some regions face challenges in adopting sustainable practices due to limited resources and infrastructure. However, increasing global pressure and partnerships with international organizations are gradually influencing policy frameworks. Initiatives focusing on education, technology transfer, and incentivizing sustainable practices are emerging, aiming to balance agricultural productivity with environmental stewardship. Implications to Theory, Practice and Policy: Environmental policy theory, institutional theory and socio-technical transitions theory may be used to anchor future studies on assessing the impact of environmental regulations on sustainable livestock farming practices in Pakistan. In terms of practical implementation, promoting technological innovation is key. Collaborating with industry stakeholders to research and develop innovative technologies and practices that facilitate compliance with environmental regulations while enhancing farm productivity and resilience will be crucial. From a policy perspective, enhancing regulatory stringency and incentivizing sustainable practices are paramount.